Laser-driven photo-transmutation of 129I - A long-lived nuclear waste product - Ledingham, K; Magill, J; McKenna, P; Yang, J; Galy, J; Schenkel, R; Rebizant, J; McCanny, T; Shimizu, S; Robson, L; Singhal, R; Wei, MS; et al. (2003)
Intense laser-plasma interactions produce high brightness beams of gamma rays, neutrons and ions and have the potential to deliver accelerating gradients more than 1000 times higher than conventional accelerator technology, and on a tabletop scale. This paper demonstrates one of the exciting applications of this technology, namely for transmutation studies of long-lived radioactive waste. We report the laser-driven photo-transmutation of long-lived 129I with a half-life of 15.7 million years to 128I with a half-life of 25 min. In addition, an integrated cross-section of 97±40 mbarns for the reaction 129I(γ,n)128I is determined from the measured ratio of the (γ,n) induced 128I and 126I activities. The potential for affordable, easy to shield, tabletop laser technology for nuclear transmutation studies is highlighted.